(untitled) (International Journal of Technology and Management Research, 2020)
This paper investigated the reflections of Electoral Commission (EC) officers and voters in the Jaman South District with regard to ballot paper wastage in elections in Ghana using descriptive exploratory research design. Purposive and convenience sampling techniques were used to select 172 respondents for the study with questionnaires, structured interview and interview guide as the research instruments. The study revealed that elections were conducted to help select leaders for the nation and to help ensure that leaders are accountable to the people. Policies and ideologies of candidates were found to have little influence on how persons vote. Factors such as protest voting, low public education on elections, and high level of illiteracy were responsible for rejected ballots in the district. Rejected ballot paper was a cost to the EC officers and the voters in terms of resources, time and energy especially during periods of run-offs. The study recommended that the government effectively collaborate with the EC officials in the district to implement policies that will increase voters’ appreciation of issues underpinning democracy. The EC officers in the district should properly collaborate with the National Commission for Civic Education (NCCE) to provide adequate public education to enable the electorates in the district to have a proper understanding of basic electoral issues. Key words: Elections; democracy; democratization; disenfranchisement; rejected ballots.